2022
DOI: 10.1155/2022/4152841
|View full text |Cite
|
Sign up to set email alerts
|

Variation Pattern of the Stress‐Strain Curve of Concrete under Multifactor Coupling

Abstract: The air shafts of coal mines contain solid, liquid, and gaseous substances that corrode concrete under conditions of relatively high temperature and humidity. The coupling of various factors decreases the concrete strength and thus the bearing capacity of the air shaft lining. In this study, concrete corrosion tests were carried out by simulating the complex environment of a coal mine air shaft lining to study the variation in the concrete stress-strain curve. For corroded concrete specimens subjected to very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…The results showed that as long as the strength of steel reaches 980 MPa, the error of the stress–strain curve predicted by the model was within 100 MPa in most cases. Xie et al 20 analyzed and predicted the variations of stress–strain curve of concrete under multi-factor coupling by using parametric equation method. However, the general steps such as the establishment of mathematical models or mathematical equations are complicated, and the most important thing is that the efficiency and accuracy need to be improved, so it is urgent to develop a low-cost, high-accuracy stress–strain curve prediction method.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that as long as the strength of steel reaches 980 MPa, the error of the stress–strain curve predicted by the model was within 100 MPa in most cases. Xie et al 20 analyzed and predicted the variations of stress–strain curve of concrete under multi-factor coupling by using parametric equation method. However, the general steps such as the establishment of mathematical models or mathematical equations are complicated, and the most important thing is that the efficiency and accuracy need to be improved, so it is urgent to develop a low-cost, high-accuracy stress–strain curve prediction method.…”
Section: Introductionmentioning
confidence: 99%